Thrombolysis in patients with prior stroke within the last 3 months. (17th July 2014) - Heldner, M. R.; Mattle, H. P.; Jung, S.; Fischer, U.; Gralla, J.; Zubler, C.; El‐Koussy, M.; Schroth, G.; Arnold, M.; Mono, M.‐L.
<x xml:space="preserve">Abstract</x> Background and purpose Patients with prior stroke within 3 months have been mostly excluded from randomized thrombolysis trials mainly because of the fear of an increased rate of symptomatic intracerebral hemorrhage (sICH). The aim of this study was to compare baseline characteristics and clinical outcome of thrombolyzed patients who had a previous stroke within the last 3 months with those not fulfilling this criterion (comparison group). Methods In all, 1217 patients were included in our analysis (42.2% women, mean age 68.8 ± 14.4 years). Results Patients with previous stroke within the last 3 months (17/1.4%) had more often a basilar artery occlusion (41.2% vs. 10.8%) and less frequently a modified Rankin scale (mRS) score 0–1 prior to index stroke (88.2% vs. 97.3%) and a higher mean time lapse from symptom onset to thrombolysis (321 min vs. 262 min) than those in the comparison group. Stroke severity was not different between the two groups. Rates of sICH were 11.8% vs. 6%. None of the sICHs and only one asymptomatic intracerebral hemorrhage occurred in the region of the former infarct. At 3 months, favorable outcome (mRS ≤ 2) in patients with previous stroke within 3 months was 29.4% (vs. 48.9%) and mortality 41.2% (vs. 22.7%). Conclusions In patients with prior stroke within the last 3 months, none of the sICHs and only one asymptomatic intracerebral hemorrhage occurred in the region of the former infarct. The high mortality was influenced by four patients, who died until discharge due to acute major index stroke. It is reasonable to include these patients in randomized clinical trials and registries to assess further their thrombolysis benefit−risk ratio.